Compensation and employee performance: mediation of work motivation - Sumarjo, Wahid; Haerofiatna, Haerofiatna; Wirtadipura, Dian; Tajudin, Tajudin (Institute of Computer Science (IOCS), 2025)
This study aims to analyze the relationship between compensation provided by the company and employee performance by considering the mediating role of work motivation. The method used in this study is a quantitative approach using a questionnaire distributed to employees with a total sample of 97 people. In data processing, this study uses SmartPLS 4 to test measurement models and structural models. The results of the analysis showed that there was a significant positive relationship between compensation and employee performance. In addition, the study also found that work motivation plays a role as a mediator that strengthens the relationship between compensation and performance. These findings provide important implications for human resource management, where improving a fair and adequate compensation system can improve work motivation and, ultimately, overall employee performance. Therefore, an effective compensation management strategy should be a priority for companies looking to improve their employees' performance